Theory of oscillations in the STM conductance resulting from subsurface defects (Review Article) - Avotina, Ye.S.; Kolesnichenko, Yu.A.; Ruitenbeek, J.M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
In this review we present recent theoretical results concerning investigations of single subsurface defects by means of a scanning tunneling microscope (STM). These investigations are based on the effect of quantum interference between the electron partial waves that are directly transmitted through the contact and the partial waves scattered by the defect. In particular, we have shown the possibility imaging the defect position below a metal surface by means of STM. Different types of subsurface defects have been discussed: point-like magnetic and nonmagnetic defects, magnetic clusters in a nonmagnetic host metal, and nonmagnetic defects in a s-wave superconductor. The effect of Fermi surface anisotropy has been analyzed. Also, results of investigations of the effect of a strong magnetic field to the STM conductance of a tunnel point contact in the presence of a single defect has been presented.